2019
DOI: 10.31487/j.jicoa.2019.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic modulation related to prayer may contribute to the reduced cardiovascular mortality associated with religiosity/spirituality

Abstract: Cardiovascular disease is the leading cause of morbidity and mortality worldwide. During the past few decades, several studies have demonstrated an association between religiosity/spirituality and beneficial effects on mental and physical health. Longitudinal studies have found significant association between regular attendance at religious services and reduced all-cause and cardiovascular mortality. Among the several potential pathways of higher religiosity/spirituality, there are biological mechanisms such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…34 In a recent review, it was reported that parasympathetic activation is high and sympathetic activation is low in religious people, and they also have low cortisol levels. 35 Doufesh et al 3 studied the effect of salat activity on the autonomic nervous system in a study conducted with 30 Muslim men. As a result of the study, the researchers found that salat activity increased the parasympathetic activity and suppressed the sympathetic activity The results of this study revealed that pain sensation decreased in both groups, but this decrease was caused by the PT.…”
Section: Discussionmentioning
confidence: 99%
“…34 In a recent review, it was reported that parasympathetic activation is high and sympathetic activation is low in religious people, and they also have low cortisol levels. 35 Doufesh et al 3 studied the effect of salat activity on the autonomic nervous system in a study conducted with 30 Muslim men. As a result of the study, the researchers found that salat activity increased the parasympathetic activity and suppressed the sympathetic activity The results of this study revealed that pain sensation decreased in both groups, but this decrease was caused by the PT.…”
Section: Discussionmentioning
confidence: 99%
“…In prayer, a person may gain spiritual support, collaborate with God to solve the problem, and shift their attention to God or religious activities. However, the mechanisms underlying praying in cardiovascular disease is unknown [9]. It is also uncertain if people with a stronger belief in God's power will respond to intervention (e.g., mindful praying) in the same way as those with a weaker belief in God's power.…”
Section: Mindfulness Religion and Health Carementioning
confidence: 99%